A systematic review and meta-analysis of the effectiveness of food safety education interventions for consumers in developed countries. (December 2015) - Young, Ian; Waddell, Lisa; Harding, Shannon; Greig, Judy; Mascarenhas, Mariola; Sivaramalingam, Bhairavi; Pham, Mai; Papadopoulos, Andrew
Abstract Background Foodborne illness has a large public health and economic burden worldwide, and many cases are associated with food handled and prepared at home. Educational interventions are necessary to improve consumer food safety practices and reduce the associated burden of foodborne illness. Methods We conducted a systematic review and targeted meta-analyses to investigate the effectiveness of food safety education interventions for consumers. Relevant articles were identified through a preliminary scoping review that included: a comprehensive search in 10 bibliographic databases with verification; relevance screening of abstracts; and extraction of article characteristics. Experimental studies conducted in developed countries were prioritized for risk-of-bias assessment and data extraction. Meta-analysis was conducted on data subgroups stratified by key study design-intervention-population-outcome categories and subgroups were assessed for their quality of evidence. Meta-regression was conducted where appropriate to identify possible sources of between-trial heterogeneity. Results We identified 79 relevant studies: 17 randomized controlled trials (RCTs); 12 non-randomized controlled trials (NRTs); and 50 uncontrolled before-and-after studies. Several studies did not provide sufficient details on key design features (e.g. blinding), with some high risk-of-bias ratings due to incomplete outcome data and selective reporting. We identified a moderate to high confidence in results from two large RCTs investigating community- and school-based educational training interventions on behaviour outcomes in children and youth (median standardized mean difference [SMD] = 0.20, range: 0.05, 0.35); in two small RCTs evaluating video and written instructional messaging on behavioural intentions in adults (SMD = 0.36, 95 % confidence interval [CI]: 0.02, 0.69); and in two NRT studies for university-based education on attitudes of students and staff (SMD = 0.26, 95 % CI: 0.10, 0.43). Uncontrolled before-and-after study outcomes were very heterogeneous and we have little confidence that the meta-analysis results reflect the true effect. Some variation in outcomes was explained in meta-regression models, including a dose effect for behaviour outcomes in RCTs. Conclusions In controlled trials, food safety education interventions showed significant effects in some contexts; however, many outcomes were very heterogeneous and do not provide a strong quality of evidence to support decision-making. Future research in this area is needed using more robust experimental designs to build on interventions shown to be effective in uncontrolled before-and-after studies.